PLTS 200 Wp to Meet Energy Needs at the Taqwa Muhammadiyah Mosque, Sei Litur Village, Sawit Sebrang Langkat District - Partaonan Harahap; Irfan Nofri; Sudirman Lubis (Faculty of Smart Technology and Engineering, Universitas Kristen Maranatha, Bandung, Indonesia, 2021)
At the Taqwa Muhammadiyah Mosque, a local place of worship, the power blackout is becoming very troublesome. On one side of the village where the research was conducted, the light intensity was high enough so that it is very good to be used as a source of renewable energy, namely solar panels or better known as PLTS. Method used in this research is experiment which is fully functional to control the implementation of the solar panel for electricity supply for the Mosque everyday activity Based on the results of measurements and calculations, the 200 Wp solar panel, when the weather is sunny, will be able to charge a battery by 68.2% or 87.2 Watts. In using the battery, the efficiency factor of the battery must be considered because it cannot be operated until all power is used up. Battery Capacity is 754.7 Ah and is able to supply DC lamps for 1 day and is able to supply AC loads for 1.02 day. So in 11 hours (lowest data) the 200WP solar panel is able to charge a battery with a capacity of 100Ah at 80% of the full battery capacity. Keywords: generator; PLTS; solar cell